AN ANALYSIS OF STUDENTS’ PROBLEM IN TRANSLATING NARRATIVE TEXT IN IAIN LHOKSEUMAWE - zainuddin zainuddin hasibuan (English Education Department at FKIP Nommensen University, 2020)
ABSTRACT Research purpose is to find out students’ problem in translating English narrative text. This research used descriptive qualitative approach and research design as a case study. Research result were the writer found that the students had many problems in translating narrative text. Their problem were in the form of understanding meaning such as: lexical meaning, grammatical meaning, contextual meaning, textual meaning, and socio – cultural meaning. The most problem owned by students it was about lexical meaning because they had lack of vocabulary and they did not have a rellevant dictioanary that they would use when they translated narrative text into Indonesian language as target of language. The students had difficulties in understanding about English structure that different with Indonesian structure as target of language when they did translating of text, so, the students got confused to organize meaning. The students also had any obstacle with English pattern that was different with Indonesian pattern, when they translated, they were confused because they should change word position. Additionallay, they translated the narrative text words by words based on position of words that was appeared in target of language. It was also influenced by internal and external factors.